2014
DOI: 10.1007/s00223-014-9916-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Exposure to the Endocrine Disruptor, Methoxychlor, Reduces Lean Body Mass and Bone Mineral Density and Increases Cortical Porosity

Abstract: Endogenous estrogen has beneficial effects on mature bone and negatively affects the developing skeleton, whereas the effect of environmental estrogens is not known. Methoxychlor (MXC) is a synthetic estrogen known as a persistent organochlorine and used as a pesticide. Methoxychlor and its metabolites display estrogenic, anti-estrogenic and anti-androgenic activity and may therefore influence bone. Fifty-eight male fetal and neonatal rats were exposed to either: a negative control (DMSO), 0.020, 100 mg/kg MXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Of all exogenous estrogen studies, the effects of BPA in our study are most similar to those following an acute administration of EB on PND1 ( Table 2 ), which resulted in male-specific reductions in bone mass and strength, while females were unaffected [ 37 ]. A second study using a greater dose of EB coupled with a longer exposure again resulted in reduced bone mass in males but did not translate to significant changes in bone function [ 38 ]. In addition to technical variability in study design, the hallmark nonmonotonic nature of EDCs supports the possibility of distinct effects at different doses [ 2 , 22 , 23 ].…”
Section: Exogenous Estrogens Induce Overlapping But Distinct Effects mentioning
confidence: 99%
See 1 more Smart Citation
“…Of all exogenous estrogen studies, the effects of BPA in our study are most similar to those following an acute administration of EB on PND1 ( Table 2 ), which resulted in male-specific reductions in bone mass and strength, while females were unaffected [ 37 ]. A second study using a greater dose of EB coupled with a longer exposure again resulted in reduced bone mass in males but did not translate to significant changes in bone function [ 38 ]. In addition to technical variability in study design, the hallmark nonmonotonic nature of EDCs supports the possibility of distinct effects at different doses [ 2 , 22 , 23 ].…”
Section: Exogenous Estrogens Induce Overlapping But Distinct Effects mentioning
confidence: 99%
“…1 ) and in vertebrae [ 36 , 39 ]. In studies that have assessed bone mass and strength in multiple bone types ( Table 2 ), vertebrae are often the most susceptible to exposure [ 9 , 29 , 36 , 38 , 40 ]. Future BPA studies, therefore, would benefit from more comprehensive investigations of cortical and cancellous bone health in male and female offspring.…”
Section: Exogenous Estrogens Induce Overlapping But Distinct Effects mentioning
confidence: 99%
“…In this study, MCX exposure during embryonic and postnatal development reduced body weight and bone size; moreover cortical porosity resulted negatively affected compared to control. MXC might act as an ERβ antagonist, thus inhibiting the proper mineralization of the developing skeleton, however significant differences may be observed in different species (Fagnant et al, 2014). In addition, it should be considered that the major metabolite of MXC, hydroxyphenyltrichloroethane (HPTE), is even more potent than MCX as an EDC (Uzumcu et al, 2006).…”
Section: Synthetic Xenoestrogens: Endocrine Disrupting Chemicals (mentioning
confidence: 99%
“…Human epidemiological and rodent model studies have shown that constant exposure to MXC during adulthood affects cycling and ovulation and leads to fertility issues . Several studies have indicated that MXC can have a developmental programming effect, causing alterations in epigenetic processes, such as changes in methylation patterns . When rodents are exposed to MXC during foetal or early postnatal life, the effects in females persist until adulthood, with alterations in reproductive outcomes, such as puberty acceleration, an irregular oestrous cycle, and alterations in folliculogenesis and cyst formation.…”
Section: Endocrine Disruptorsmentioning
confidence: 99%